Word-Finding Difficulties as a Prominent Early Finding in a Later Diagnosis of Attention Deficit Hyperactivity Disorder - Ganelin-Cohen, Esther; Pilowsky Peleg, Tammy; Leibovich, Noa; Bachrachg, Esther; Watemberg, Nathan (Neuropediatrics, 2023)
Objective Attention deficit hyperactivity disorder (ADHD) is a common neuropsychological disorder primarily diagnosed in childhood. Early intervention was found to significantly improve developmental outcomes, implicating on the role of early identification of ADHD markers. In the current study, we explored the developmental history of children referred to neurological assessment to identify early ADHD predictors.Methods A total of 92 children and adolescents (41 females) recruited at a pediatric neurology clinic, with suspected ADHD (n = 39) or other neurological difficulties (n = 53) such as headaches, seizures, tic disorders, orthostatic hypotension, postischemic stroke, intermittent pain, and vasovagal syncope. Developmental history information was obtained from caregivers, and evaluation for possible ADHD was performed. Developmental details were compared between children with and without current ADHD diagnosis.Results Word-finding difficulties (WFDs) in preschool age was reported in 30.4% of the sample. Among children diagnosed with ADHD, 43% had WFDs history, compared with only 5% in children without ADHD. Among children with WFDs history, 93% were later diagnosed with ADHD compared with 42% in children without WFDs history. The relationship between WFDs and ADHD was significant (chi-square test [1, N = 92] = 20.478, p < 0.0001), and a logistic regression model demonstrated that asides from a family history of ADHD, the strongest predictor for ADHD in school age children was a history of WFDs.Conclusion Preliminary evidence supports a predictive link between preschool WFDs and later ADHD diagnosis, highlighting the importance of early WFDs clinical attention.
Keywords: attention-deficit hyperactivity disorder; word-finding difficulty; language; disability; child development